2021
DOI: 10.1038/s41598-021-85421-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of plasma tRNA fragments as a promising biomarker for liver fibrosis in nonalcoholic fatty liver disease

Abstract: Fibrotic tissue remodelling in nonalcoholic fatty liver disease (NAFLD) will probably emerge as the leading cause of end-stage liver disease in the coming decades, but the ability to diagnose liver fibrosis in NAFLD patients noninvasively is limited. The abnormal expression of tRNA-derived small RNA (tsRNA) in plasma provides a novel idea for noninvasive diagnosis of various diseases, however, the relationship between tsRNAs and NAFLD is still unknown. Here, we took advantage of small RNA-Seq technology to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The presence of stable tsRNAs in human serum has been confirmed by recent studies (26). Expression profile of serum tsRNAs can be potential fingerprints for various diseases (29)(30)(31). To identify the tsRNA profile in SLE patients, all participants were divided into three groups according to the clinical standard, including SLE without LN, SLE with LN, and healthy control.…”
Section: Ectopic Serum Tsrna Profiles In Systemic Lupus Erythematosus Patientsmentioning
confidence: 94%
“…The presence of stable tsRNAs in human serum has been confirmed by recent studies (26). Expression profile of serum tsRNAs can be potential fingerprints for various diseases (29)(30)(31). To identify the tsRNA profile in SLE patients, all participants were divided into three groups according to the clinical standard, including SLE without LN, SLE with LN, and healthy control.…”
Section: Ectopic Serum Tsrna Profiles In Systemic Lupus Erythematosus Patientsmentioning
confidence: 94%
“…[ 33 ] Recently, several studies have indicated that circulating tDRs could serve as potential biomarkers for cancer diagnosis, prognosis after oncological therapies, monitoring cancer progression, liver fibrosis diagnosis, and distinguishing between subtypes of acute stroke. [ 24 , 34 ] Because conventional methods for detecting tDRs may underestimate the diversity and abundance of extracellular tDRs, building the stress‐specific extracellular tDR signatures using specialized tDR sequencing techniques promises to provide new markers of cellular processes associated with disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…tsRNA is a non-coding small RNA which involved in a variety of physiological and pathological processes. It has been identified as a new class of NAFLD biomarkers due to the significant increase of tsRNAs in plasma of NAFLD patients [ 45 ]. Interestingly, we have previously reported that tsRNAs regulated autophagy, which played an important role in NASH [ 17 ].…”
Section: Discussionmentioning
confidence: 99%